PENGGUNAAN BUKU PANDUAN PERTOLONGAN PERTAMA RAMAH ANAK TERHADAP KETERAMPILAN MENANGANI LUKA DALAM RANGKA MEWUJUDKAN SEKOLAH SEHAT - Putra, Adi; Hasanah, Uswatun; Yuliati, Siti Rohmi; Januar, Ahmad (Jurnal Pendidikan Dasar, 2022)
First Aid in Accidents is an effort to help and temporary care for accident victims before getting more perfect help from a doctor or paramedic. This study aims to test the effectiveness of the use of child-friendly first aid manuals on students' skills in dealing with injuries in realizing healthy schools. The book's effectiveness will determine the success of using the first aid book in creating a healthy school. The higher the level of effectiveness, the more functionality and usefulness the module. From the results of the study, it was found that the student's skills improved after using this first-aid manual. Thus, this child-friendly first aid book is very suitable as a supporting book for sports education teachers in order to realize healthy schools. This study's results can motivate teachers always to practice student skills in first aid so students can help those around them.